2018
DOI: 10.18203/2320-6012.ijrms20181771
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anaesthetic techniques for caesarean

Abstract: Background: The anaesthetic technique to be used in Caesarean section is determined according to factors such as urgency, presence of coexisting health problems, preference of patient and preference and experience of the anaesthetist and surgeon.Methods: This is a retrospective study of all the caesarean deliveries that occurred in the period between 1st Jan 2010 to 31st Dec 2017 in the department of obstetrics and Gynaecology in Silchar Medical College. The anaesthesia techniques used for caesarean sections w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Techniques of anesthesia are under the influence of many factors include, nature of the procedure, patient's medical condition, patient's preference, anesthesia providers' experience, and availability of the resources and the communication of anesthesia provider with parturient about the advantage and disadvantages of each anesthesia techniques. [6][7][8][9] Patients having surgical procedures have varying levels of awareness about anesthesia and anesthesia techniques. The result of study conducted by Irfan ali kadri et al 2014 showed, 63% of patients were unaware of anesthesia techniques while in another study, 48.1% of patients were aware.…”
Section: Introductionmentioning
confidence: 99%
“…Techniques of anesthesia are under the influence of many factors include, nature of the procedure, patient's medical condition, patient's preference, anesthesia providers' experience, and availability of the resources and the communication of anesthesia provider with parturient about the advantage and disadvantages of each anesthesia techniques. [6][7][8][9] Patients having surgical procedures have varying levels of awareness about anesthesia and anesthesia techniques. The result of study conducted by Irfan ali kadri et al 2014 showed, 63% of patients were unaware of anesthesia techniques while in another study, 48.1% of patients were aware.…”
Section: Introductionmentioning
confidence: 99%